Analisis Penggunaan Tata Bahasa dan Pemerolehan Bahasa Kedua Bahasa Inggris pada Mahasiswa Thailand - Minkhatunnakhriyah Minkhatunnakhriyah; Fahriany Fahriany; Albiansyah Albiansyah (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
Abstract: This paper aims to determine the types of grammar usage and todescribe the acquisition of English as a second language among Thaistudents. The method used was a qualitative paradigm and the data sourceswere taken from interviews. The interview instrument was used to obtainthe data in the form of English text production, which was used to identifyand to classify the types of grammar elements and information on howinformants acquire the language. This study results in variations in the useof grammar elements namely simple present tense, simple past tense,degree of comparison, noun phrases, and auxiliary verbs. The results of theinterview show that the process of mastery of a second language wasobtained through watching films in English or films with English subtitles,reading novels in English, and listening to English songs. Keywords: English Grammar; Second Language Acquisition; Speaking